The impact of allergic contact dermatitis on the inflammatory response and repair in wound healing process - Zhang, Wei; Xu, Jiabao; Qu, Songyan; Peng, Hui (Frontiers in Medicine, 2025)
BackgroundSkin trauma and the subsequent wound healing process present significant challenges for healthcare systems and patients globally. Allergic contact dermatitis (ACD) was a delayed-type hypersensitivity reaction that can disrupt the normal wound repair process due to prolonged inflammation and immune dysregulation. However, the specific impact of ACD on the inflammatory response and repair in wound healing remains incompletely understood. This study aimed to investigate the influence of ACD on the inflammatory response and repair during the wound healing process.MethodsThis study was a retrospective cohort study. A total of 120 patients with skin trauma treated at Henan Provincial People’s Hospital from January 2023 to December 2023 were included. There were 69 cases of control and 51 cases of ACD. Inclusion and exclusion criteria were defined, and various indicators, including patient data, inflammatory factors, cell detection, and wound healing assessment, were measured and analyzed using appropriate statistical methods.ResultsThe study revealed significant differences between the control and ACD groups. ACD was associated with higher levels of TNF-α, IL-6, IL-1β, C-reactive protein, and IL-8 compared to control (p < 0.05). Additionally, ACD group exhibited increased counts of macrophages, neutrophils, T lymphocytes, B lymphocytes, and mast cells compared to the control group (p < 0.05). Moreover, ACD was linked to delayed wound closure time and differences in the distribution of healing degrees (p < 0.05). Correlation analysis indicated significant associations among ACD, inflammatory markers, cellular responses, wound closure time, and healing degree (p < 0.05).ConclusionThe study demonstrates that ACD exerts a substantial impact on the inflammatory response, cellular components, and wound healing parameters in the context of skin trauma. The heightened levels of inflammatory markers, altered cellular responses, and delayed wound closure observed in ACD patients underscore the need for targeted interventions tailored to optimize wound repair in this population.